Development of an innovative mathematical model to design an active modified atmosphere storage system for mango (cv. Amrapali). (6th November 2021) - Thakur, Rajeev Ranjan; Mangaraj, Shukadev
Abstract: Currently, the modified atmosphere storage (MAS) technique is one of the most economical and widely adopted practices used to enhance the shelf life of fresh produce including mango. The MAS system is designed in two ways; one is called passive MAS and other is active MAS. Nowadays the bulk handling and storage of fresh produce at on‐farm level is one of the challenging tasks and therefore, using the basic principle of modified atmosphere packaging (MAP) the study was aimed to develop an active MAS system. In this study, to design an active MAS system for 100 kg of mango, an innovative active mathematical model was developed using enzyme kinetics‐based respiration rate model coupled with Arrhenius equation under active condition (50, 100, and 150 cc of O2 absorber). The designed active system was used for on‐farm handling and storage of mango at 27°C. The basic aim of the model was to determine the exact quantity of oxygen absorber required to bring early dynamic equilibrium condition inside the MAS system with optimum level of gas concentration (5–8% O2 and 5–8% CO2 ) for mango. The model was solved by Adam's numerical method using Taylor's formulae and iterated in MATLAB software. The mean relative percentage deviation moduli ( E ) between the experimental and predicted values of O2 and CO2 concentration was found to be 8.97 and 8.42%, respectively, indicating the accuracy of the developed active model. Practical applications: On‐farm handling of fresh horticultural crops is the leading problem for orchard growers and causes excess postharvest losses. The current work presents some interesting results on the determination of the exact concentration of oxygen absorber required to design an accurate as well as a perfect active modified atmosphere storage system for 100 kg of mango using the concept of mathematical modeling. The principle aim of this approach was to increase the adaptability of the modified atmosphere packaging concept for preservation and shelf life extension of fresh produce during bulk handling and transportation. The designed system is easy to handle mango during its on‐farm storage and might become a boon for orchard growers. Abstract : Flow chart depicting stepwise procedure to develop and validate innovative mathematical model used to design active modified atmosphere storage (MAS) system.